1973
DOI: 10.1128/jb.113.3.1121-1126.1973
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Lipids of Six Strains of Bacteroides ruminicola

Abstract: The lipids of six strains of Bacteroides ruminicola were characterized. The nonpolar lipid accounted for 6 to 24% of the total lipid and was composed of diglycerides, triglycerides, and free fatty acids. The phospholipid fraction contained phosphatidylethanolamine, phosphosphingolipids, and trace quantities of phosphatidic acid. In three strains the phosphosphingolipid fraction made up more than half of the total lipid. The fatty acids in the nonpolar, acyland phosphosphingolipid consisted of a homologous seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Sphingolipids have been rare components in bacterial membrane systems, although ceramide phosphorylethanolamine and ceramide phosphorylglycerol were present in Bacteroides melaninogenicus, an absolutely anaerobic rumen bacterium [1][2][3]. They contain C16, C~7, C~8 and C~9 long-chain bases among which the branchedchain C19 and normal Cjs sphinganine predominate [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingolipids have been rare components in bacterial membrane systems, although ceramide phosphorylethanolamine and ceramide phosphorylglycerol were present in Bacteroides melaninogenicus, an absolutely anaerobic rumen bacterium [1][2][3]. They contain C16, C~7, C~8 and C~9 long-chain bases among which the branchedchain C19 and normal Cjs sphinganine predominate [14].…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipids are known to be among the important components of membrane lipids in higher animals and plants. In contrast, they are extremely rare in prokaryotic cells and reported to occur in only limited genera of bacteria [1][2][3][4][5][6]. Previously, we have found that the cellular lipids of Flavobacterium devorans ATCC10829, which belongs to the Pseudomonas-like group IIK-type 1, contained a unique sphingoglycolipid, ceramide glucuronic acid [7].…”
Section: Introductionmentioning
confidence: 99%
“…Gas-liquid chromatography was performed with a Perkin Elmer model 881 gas chromatograph equipped with glass colums (1.8m) containing 10% SP-2340 or 10% SP-2330 on 100/120 Chromosorb W (Supelco Inc., Bellefonte, Pa.) as outlined by Kunsman (1973).…”
Section: Because Of Recent Decisions Made By the Animal And Plantmentioning
confidence: 85%
“…No further separation of the cerebrosides and sulfatides were attempted. The polar lipids were separated and quantified by two-dimentional thinlayer chromatography on RediCoats (Supelco, Inc., Bellefonte, Pa.) (Kunsman, 1973).…”
Section: Because Of Recent Decisions Made By the Animal And Plantmentioning
confidence: 99%
“…Sphingolipids are already established to be important components in membrane lipids of higher organisms. However, they are extremely rare in bacterial cells and reported to occur only in limited genera [1][2][3][4][5][6]. Previously, we have reported that strains of Pseudomonas such as group II-K type 2, a Gram-negative, aerobic, opportunistic pathogen, contained sphingophospholipids [7,8] and there-fore, Yabuuchi et al [9] placed the organism in a new genus.…”
Section: Introductionmentioning
confidence: 99%